Electrolyte, preparation method thereof and battery
By mixing the temperature-displaying material into the electrolyte and dispersing it inside the battery, and using the color change of temperature changes to calibrate the internal temperature of the battery, the problem of being unable to comprehensively monitor the internal temperature of the battery in the existing technology is solved, and the internal temperature of the battery is accurately measured. Monitoring and protection of battery performance.
Patent Information
- Application Number
- CN202410798691.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-20
AI Technical Summary
The prior art is difficult to fully monitor the internal temperature distribution of the battery, especially in the welding position and the shell wall, and the battery production process with temperature sensing lines is complicated.
The temperature-indicating material is mixed into the electrolyte, and the temperature-indicating material is dispersed to various parts of the battery through the flow of the electrolyte. The color change of the temperature-indicating material with temperature changes is used to calibrate the maximum temperature of different parts inside the battery.
It achieves comprehensive detection of the internal temperature of the battery and can accurately reflect the temperature conditions everywhere inside the battery without deteriorating the battery performance and the process is simple.
Smart Images

Figure CN118380675B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to an electrolyte, a preparation method thereof and a battery. Background Art
[0002] Batteries have been widely used as power sources for equipment in various fields due to their high energy density, long life and pollution-free properties. However, while batteries excel in high energy density, lightweight design and long life, they also present some potential safety risks. Monitoring their internal temperature distribution can help discover potential safety hazards as soon as possible.
[0003] At present, the temperature of different locations inside the battery is usually studied by pre-embedded temperature sensing wires before sealing, and using external circuits for research. Specifically: using external circuits to collect data to reflect the temperature changes at a certain location inside the battery. This method can only select a limited number of points for testing each time, which cannot fully reflect the temperature distribution inside the battery, and there are large accidental errors during the test process, and the batch stability is poor. In addition, batteries with temperature sensing wires also have the problem of complex manufacturing processes.
[0004] The invention patent with publication number CN 115224436A provides a method for preparing a lithium-ion battery diaphragm, using irreversible temperature-sensitive material particles coated on the surface of the diaphragm, and using the color-changing characteristics of the temperature-sensitive material to study the distribution of the temperature inside the battery. The invention patent with publication number CN 113948820A provides a lithium-ion battery composite diaphragm that includes microcapsules made of temperature-sensitive materials and a composite diaphragm made of inorganic nanomaterials. On the one hand, the presence of inorganic nanomaterials can enhance the thermal safety of the battery cell, and on the other hand, the presence of temperature-sensitive materials can also determine the highest temperature at different locations inside the battery cell. However, the monitoring method through the diaphragm has the following disadvantages: first, it will increase the internal resistance of the diaphragm, increase the total battery internal resistance and heat generation, and cause test errors; second, it cannot fully detect the temperature inside the battery, especially at the welding position and the shell wall. Therefore, it is necessary to provide a new solution to achieve monitoring of the temperature distribution inside the battery. Summary of the invention
[0005] The present invention aims to solve the above-mentioned problem and provides an electrolyte, a preparation method thereof and a battery. A temperature indicating material is mixed into the electrolyte. The temperature indicating material is dispersed to various parts of the battery through the flow of the electrolyte. The temperature indicating material undergoes irreversible changes in its color as the temperature changes, so as to calibrate the maximum temperature reached in different parts of the battery. The temperature inside the battery can be fully detected without deteriorating the battery performance.
[0006] According to the technical solution of the present invention, the electrolyte includes a basic electrolyte and temperature indicating particles. The temperature indicating particles are of a core-shell structure, including a temperature indicating material and a shell that wraps the temperature indicating material. The shell is insoluble in the basic electrolyte.
[0007] Furthermore, the mass ratio of the temperature indicating particles to the basic electrolyte is 1:10-20.
[0008] Furthermore, the D50 of the temperature indicating particles is 10-60 μm.
[0009] Furthermore, the temperature indicating material is an irreversible temperature-sensitive material, which can record the highest temperature reached at the location of the temperature indicating material, and the temperature indicating material includes copper sulfate and manganese sulfate; wherein the mass ratio of copper sulfate to manganese sulfate can be 4:6-6:4.
[0010] Furthermore, the shell includes polymethyl methacrylate.
[0011] The second aspect of the present invention provides a method for preparing the above-mentioned electrolyte, comprising the following steps:
[0012] S1: mixing an aqueous solution of a temperature indicating material with a polymethyl methacrylate solution to obtain an inner emulsion;
[0013] S2: adding the inner emulsion to the outer emulsion for emulsification to obtain a mixed solution, wherein the outer emulsion is an oil phase solvent containing an emulsifier;
[0014] S3: performing rotary evaporation on the mixed solution, standing for stratification, and removing the oil layer to obtain a thermometric particle emulsion;
[0015] S4: separating and drying the temperature-indicating particle emulsion to obtain temperature-indicating particles;
[0016] S5: dispersing the temperature indicating particles in a basic electrolyte to obtain the electrolyte.
[0017] Furthermore, in the aqueous solution of the temperature indicating material, the content of the temperature indicating material is 10-20wt%.
[0018] Furthermore, in the polymethyl methacrylate solution, the content of polymethyl methacrylate is 10-20wt%. The solvent of the polymethyl methacrylate solution is a mixed solvent of water and an organic solvent, wherein the organic solvent is selected from one or more of acetone, dimethylformamide, dimethyl sulfoxide, methylal, acetonitrile, n-heptane, polyvinyl alcohol, etc.; and the mass ratio of water to the organic solvent is 1:10-30.
[0019] Furthermore, in the inner emulsion, the mass proportion of the aqueous solution of the temperature indicating material is 33-75%.
[0020] Furthermore, the emulsifier is selected from one or more of Span80, Tween80, span85, span60, etc.; the oil phase solvent is selected from one or more of liquid paraffin, alkyl phosphate, sulfonated fatty acid ester and polyacrylate; and the content of the emulsifier in the external emulsion is 8-10wt%.
[0021] Specifically, the external emulsion can be obtained by heating the emulsifier and the oil phase solvent to 55-75° C. and mixing them evenly.
[0022] Furthermore, in step S2, the volume of the inner emulsion accounts for 30%-70% of the volume of the mixed solution.
[0023] Furthermore, in the step S2, the inner emulsion is quickly added to the outer emulsion under stirring conditions to emulsify and obtain a mixed solution.
[0024] Furthermore, the emulsification is carried out by stirring at a rotation speed of 1500-3000 r / min for 20-50 min.
[0025] Specifically, under the stirring condition of a rotation speed of 600-1000 r / min, the inner emulsion is quickly added to the outer emulsion within 1-5 seconds.
[0026] Furthermore, in step S3, the conditions for rotary evaporation are: pressure 0.9-1.2 MPa, temperature 25±5° C., and stirring speed 4000-5000 r / min.
[0027] Furthermore, in step S3, the standing time is 10-20 hours; and the oil layer (upper layer) and the turbid layer (lower layer) are obtained by standing and stratifying.
[0028] Furthermore, in step S4, the separation method is water washing.
[0029] A third aspect of the present invention provides a battery, comprising the above electrolyte or the electrolyte prepared by the above preparation method.
[0030] The technical solution of the present invention has the following advantages compared with the prior art:
[0031] Temperature detection is performed through the electrolyte. Since the electrolyte is the medium for ion migration, the temperature-indicating material is dispersed by the electrolyte. The dispersion path conforms to the dynamic principle of the battery itself. Therefore, compared with the method of directly applying the temperature-indicating material on the diaphragm, it can more accurately reflect the temperature inside the battery.
[0032] By using the existing electrolyte injection method, the temperature indicating material can be dispersed to various places of the battery by utilizing the flow of the electrolyte, without adding a coating process, the process is simple and the effect is high;
[0033] The range of studying the internal temperature of the battery is wide, and it is distributed around the battery shell wall, collector plate, pole and diaphragm. It can study the temperature distribution of the battery more comprehensively, so it can identify the temperature changes of the battery cell and the temperature changes of the mechanical structural parts of the battery cell, which is simple and flexible;
[0034] Since the electrolyte can soak the entire battery cell, it can reflect the temperature changes of the entire battery cell as a whole. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a cross-sectional view of the tab structure on both sides of a cylindrical battery.
[0036] Figure 2 The figure is a comparison chart of the cycle performance of the battery obtained in Example 1 and the battery obtained by conventional injection.
[0037] Explanation of the reference numerals: 1-shell, 2-cover, 3-cell, 4-positive electrode column, 5-positive electrode collector plate, 6-negative electrode collector plate, 7-positive electrode ear, 8-negative electrode ear, 9-sealing nail. DETAILED DESCRIPTION
[0038] The present invention provides an electrolyte, in which a temperature-indicating material is mixed into the electrolyte, and the temperature-indicating material is dispersed to various parts of the battery through the flow of the electrolyte. The temperature-indicating material undergoes irreversible changes in its own color as the temperature changes, so as to calibrate the maximum temperature reached by different parts inside the battery. The invention has the advantages of low price, fast response speed, intuitiveness, simplicity, etc. Based on the characteristics of the color change of the material due to temperature, the highest temperature point can be quickly calibrated to find the highest temperature point of the battery.
[0039] The preparation method is as follows:
[0040] (1) Weigh a certain amount of oil phase solvent (selected from one or more of liquid paraffin, alkyl phosphate, sulfonated fatty acid ester and polyacrylate) and emulsifier (selected from one or more of Span80, Tween80, span85, span60, etc.), pour them into a container, heat to 55-75° C., stir to fully dissolve, and obtain an external emulsion (emulsifier content is 8-10wt%).
[0041] (2) Weigh a temperature-indicating material (copper sulfate and manganese sulfate in a mass ratio of 4:6-6:4), dissolve it in water (the content of the temperature-indicating material is 10-20 wt%), and obtain an aqueous solution of the temperature-indicating material.
[0042] (3) Weigh polymethyl methacrylate, dissolve it in a mixture of an organic solvent (selected from one or more of acetone, dimethylformamide, dimethyl sulfoxide, methylal, acetonitrile, n-heptane, polyvinyl alcohol, etc.) and water in a mass ratio of 1:10-20, and stir and dissolve it at room temperature (25±5°C) to obtain a polymethyl methacrylate solution.
[0043] (4) The aqueous solution of the temperature indicating material obtained in step (2) and the polymethyl methacrylate solution obtained in step (3) are mixed in a mass ratio of 1:2-3:1 to obtain an inner emulsion (the content of the aqueous solution of the temperature indicating material is 33-75wt%).
[0044] (5) Under vigorous stirring (rotation speed of 600-1000 r / min), the inner emulsion is quickly (within 1-5 s) poured into the outer emulsion, and emulsified (stirred at 1500-3000 r / min for 20-50 min) to obtain a mixed solution (the volume proportion of the inner emulsion is 30%-70%).
[0045] (6) Take out the emulsified mixed solution, put it into a rotary evaporator, and perform rotary evaporation at 0.9-1.2 MPa, 25±5°C, and a stirring speed of about 4000-5000 r / min to obtain the desired original solution of the thermometric particle emulsion (microcapsule emulsion).
[0046] (7) After standing for one night (10-20 hours), the stock solution is separated into layers. The upper layer is the oil layer (containing the oil phase solvent and a small amount of empty shells of the thermometric particles, colorless), and the lower layer is the turbid layer (containing the oil phase solvent suspension of the thermometric particles and a small amount of emulsifier, pink in color), i.e., the thermometric particle emulsion.
[0047] (8) Wash the temperature-indicating particle emulsion obtained in step (7) with water to remove the temperature-indicating material that is not wrapped or not completely wrapped in the temperature-indicating particles. After drying, the temperature-indicating particles with a core-shell structure are obtained, and the size of the particles is 10-60 μm.
[0048] (9) Disperse the prepared temperature-indicating particles in the basic electrolyte at a mass ratio of 1:10-20.
[0049] The obtained electrolyte can replace common electrolyte and a battery can be prepared by a conventional battery preparation method.
[0050] The temperature distribution of the battery at different rates can be studied to see the temperature change of the battery at different rates; each rate is cycled 2-7 times. The temperature distribution of the battery can also be directly tested and studied through conventional formation, aging, and capacity separation steps.
[0051] Taking cylindrical batteries as an example, the specific steps are as follows: disassemble the cylindrical battery to obtain the shell, cover plate and battery cell, positive electrode column and positive collector plate, and negative collector plate. The temperature distribution of the inner wall of the battery shell is judged according to the different colors of the inner wall of the shell; the temperature of the positive and negative collector plates is judged according to the colors of the positive and negative collector plates; the temperature of the cover plate is judged according to the color of the cover plate; the temperature of the positive electrode column is judged according to the color of the positive electrode column; disassemble the battery cell and judge the distribution of the internal temperature of the battery cell according to the different colors of the diaphragm. Since the color change temperature of crystalline copper sulfate is low, the temperature indicating material can display temperature changes in the low temperature stage, and manganese sulfate decomposes and changes color in the high temperature stage. Therefore, the specific temperature corresponds to the color: 50≤T<70℃ corresponds to dark blue, 70≤T<90℃ corresponds to light blue, 90≤T<120℃ corresponds to light red, 120≤T<140℃ corresponds to red, and 140≤T<170, corresponds to dark red. It should be noted that for the positive electrode, its color is black or brown whether it is empty or fully charged, and the color of the temperature indicating material cannot be distinguished. The negative electrode is black when it is empty and yellow when it is fully charged. The color of the temperature indicating material cannot be distinguished. Therefore, the changes in the temperature indicating material on the surface of the positive and negative electrode plates cannot be identified.
[0052] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0053] Example 1
[0054] (I) Preparation of electrolyte
[0055] 1. Preparation of basic electrolyte:
[0056] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent; then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare a basic electrolyte.
[0057] 2. Preparation of temperature-indicating particles (microcapsules):
[0058] (1) 360 g of liquid paraffin as the oil phase solvent and 40 g of Span 80 as the emulsifier are poured into a container, heated to 60° C., and stirred to fully dissolve to obtain an external emulsion;
[0059] (2) Take 20 g of copper sulfate and 20 g of manganese sulfate, dissolve them in 250 g of water to obtain an aqueous solution of a temperature indicating material;
[0060] (3) Weigh 60 g of polymethyl methacrylate, 30 g of acetone and 410 g of water, and stir to dissolve at room temperature (25° C.) to obtain a polymethyl methacrylate solution;
[0061] (4) taking 200 g of the solution obtained in step (2) and 200 g of the solution obtained in step (3) and mixing them to obtain an inner emulsion;
[0062] (5) at a rotation speed of 800 r / min, pour the inner emulsion into the outer emulsion within 3 s, the emulsification speed is 2000 r / min, the emulsification time is 30 min, and a mixed solution is obtained;
[0063] (6) The emulsified mixed solution was taken out and placed in a rotary evaporator. The mixed solution was rotary evaporated at 1.15 MPa, 25° C., and a stirring speed of about 4500 r / min to obtain the desired stock solution of the microcapsule emulsion.
[0064] (7) After standing for 15 hours, the original solution is separated into layers and the lower layer of microcapsule emulsion is taken out.
[0065] (8) The microcapsule emulsion obtained in step (7) is washed with water to remove the temperature-indicating material that is not wrapped or not completely wrapped in the microcapsules. After drying, microcapsules with a core-shell structure are obtained, and their D50 is about 20 μm.
[0066] 3. Preparation of electrolyte:
[0067] Take 100 g of the microcapsules obtained in step (8) and 1400 g of the basic electrolyte, mix them, and disperse the microcapsules in the basic electrolyte at a speed of 120 r / min for 20 min.
[0068] (II) Preparation of batteries
[0069] 1. Preparation of positive electrode sheet:
[0070] The positive electrode active material (lithium iron phosphate), conductive agent (ketjen black), binder (PVDF) and the like are mixed in a mass ratio of 97.5:1.4:1.2, and a solvent (N-methyl-2-pyrrolidone) is added. The mixture is stirred and mixed evenly in a vacuum mixer to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, and then baked, cold pressed and die-cut to obtain a positive electrode sheet. The surface density of the coated single side of the positive electrode slurry is 30 mg / cm 2 .
[0071] 2. Preparation of negative electrode sheet:
[0072] The negative electrode active material (graphite), conductive agent (ketjen black), and binder (PVDF) were mixed in a mass ratio of 96.2:2:1.8, and deionized water was added and stirred thoroughly to obtain a uniform negative electrode slurry, which was then coated on both sides of the copper foil current collector, and then baked, cold pressed, and die-cut to obtain the negative electrode sheet. The surface density of the coated single side of the positive electrode slurry is 12.5 mg / cm 2 .
[0073] 3. Preparation of diaphragm:
[0074] A 9μm thick polyethylene diaphragm is used.
[0075] 4.Battery assembly:
[0076] First, the positive electrode sheet, the separator, and the negative electrode sheet are stacked in order to form a material strip, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and the material strip is wound to obtain a battery cell 3, the number of windings is 100, the innermost circle of the battery cell is the first circle, and the outermost circle is the 100th circle. Along the height direction of the battery cell, a positive electrode ear 7 extends from one end, and a negative electrode ear 8 extends from the other end; then, the positive electrode collector 5 and the positive electrode ear 7 are welded, and the negative electrode collector 6 and the negative electrode The electrode ear is welded 8. After the welding is completed, the battery cell 3 is placed in the shell 1, and the cover plate 2 is welded and fixed to the opening of the shell 1. Then, the positive electrode collector 5 and the positive electrode column 4 penetrating the bottom wall of the shell 1 are welded, and the negative electrode collector 6 and the cover plate 2 are welded; finally, the prepared electrolyte is injected into the interior of the battery through the injection hole on the cover plate 2. After the injection is completed, the injection hole is sealed by a sealing nail 9. After vacuum packaging, standing, forming, shaping and other processes, a battery as shown in FIG. Figure 1 The cylindrical battery shown.
[0077] (III) Battery temperature test
[0078] Select two cylindrical batteries with a voltage of 3.65V, an internal resistance of 1.6mΩ, and a capacity of 30Ah. First, use a current of 0.5C to discharge at a rate of 3C, and the cut-off current is 0.05C. Then use a current of 0.5C to charge to 4.25V, and the cut-off current is 0.05C. When charged to 100% SOC, disassemble the cylindrical battery and observe the colors of the positive collector plate, the negative collector plate, the middle of the center hole of the battery cell, the end of the center hole of the battery cell, the side wall of the shell, the bottom wall of the shell, and the positive pole; disassemble the battery cell and observe the color of the separator. Specifically, observe the color of the separator of the 25th circle of the battery cell, the separator of the 60th circle of the battery cell, and the separator of the 95th circle of the battery cell.
[0079] Example 2
[0080] Based on the cylindrical battery in Example 1, a 5C discharge rate was used for testing, and the other steps were the same as in Example 1.
[0081] Comparative Example 1
[0082] The microcapsules and the binder (PVDF) were dissolved in water at a mass ratio of 3:1 to obtain a mixed solution in which the mass ratio of the microcapsules and the binder was 30%, which was coated on the surface of a 9 μm thick polyethylene diaphragm with a coating thickness of 20 μm, baked, and wound to obtain a battery cell, which was then injected, formed, and divided into different volumes, and tested at a discharge rate of 5C (refer to Example 1 for specific operations).
[0083] Results Analysis
[0084] 1. A color and temperature comparison table based on temperature indicating materials is shown in Table 1, and the observation results of Examples 1-2 and Comparative Example 1 are shown in Table 2.
[0085] Table 1 Color and temperature comparison table
[0086]
[0087]
[0088] Table 2 Color record table of each part
[0089]
[0090] As can be seen from Table 1, in Example 1, the temperature of the center hole of the battery cell, the positive electrode column and the 60th cycle separator of the battery cell is the highest, displayed in light red, and the temperature prediction is 90°C≤T<120°C. The temperature of the positive collector plate, the negative collector plate, the 25th cycle separator of the battery cell and the 95th cycle separator of the battery cell is second, displayed in light blue, and the temperature prediction is 70°C≤T<90°C; the temperature of the shell and the cover plate is the lowest, displayed in dark blue, and the temperature prediction is 50°C≤T<70°C.
[0091] The analysis believes that:
[0092] Since the positive electrode column needs to be welded to the positive current collector plate in order to conduct the current generated inside the battery cell out of the battery through the current path of the positive current collector plate-electrode column, and the positive electrode column is small in size and has a large current flow, it generates severe heat and has a relatively high temperature.
[0093] As the main component of the electrochemical reaction, the battery cell generates a large amount of heat, so the temperature of the center hole area and the battery cell itself is not low. Furthermore, the middle and end areas of the center hole of the battery cell are both displayed in light red, indicating that the temperature difference between the two is not large. It is speculated that since the center hole is hollow, there is gas inside that can convectively dissipate heat, so the temperature of the middle end of the center hole is close. However, the temperature of the battery cell is more complicated than the temperature of the rest of the battery. In Example 1, the number of windings of the battery cell is 100. The present invention selects the color of the 25th circle of the diaphragm to represent the temperature inside the battery cell, the color of the 60th circle of the diaphragm to represent the color of the middle of the battery cell, and the color of the 95th circle of the diaphragm to represent the temperature of the edge of the battery cell, so as to explore the overall temperature distribution of the battery cell. The results show that the temperature in the middle of the battery cell is significantly higher than the temperature inside and at the edge of the battery cell. It is speculated that the heat generated in various parts of the battery cell is almost equal, and the temperature depends almost entirely on the heat dissipation conditions. The inside of the battery cell can rely on convection heat dissipation through the center hole, and the edge of the battery cell can dissipate heat outwards through its contact with the shell. However, there is no excellent heat dissipation channel in the middle of the battery cell, so the temperature in the middle of the battery cell is the highest, while the temperatures inside and at the edges are relatively low.
[0094] As for the positive collector and negative collector plates, they are the connectors between the pole lugs and poles, and their heat generation is not low, but the results show that their temperature is lower than that of the positive pole and the middle of the battery cell. It is speculated that compared with the positive pole, the positive collector and negative collector plates have a larger surface area and a larger heat dissipation area, so their temperature is lower than that of the positive pole. Compared with the battery cell, the positive collector and negative collector plates are closer to the inner wall of the shell, and the shell can be used for heat dissipation.
[0095] The shell and cover plate are the lowest temperature structural parts in the entire battery, mainly because the shell and cover plate are usually made of metal materials, and have a large heat dissipation area and fast heat transfer with the outside world. Furthermore, the shell is affected by the heat dissipation from the battery cell, so the temperature will rise, but the bottom wall area of the shell will also be affected by the heat from the positive ear, the positive collector plate and the positive column, so its temperature is higher than the temperature of the side wall of the shell, so the side wall of the shell is displayed as dark blue (darker), and the bottom wall of the shell is displayed as dark blue (lighter). Similarly, since the cover plate is affected by the heat from the negative ear and the negative collector plate, its temperature is also higher than the temperature of the side wall of the shell, so the color of the cover plate is displayed as dark blue (lighter). It should be noted that the aforementioned "lighter" and "darker" are relative to dark blue.
[0096] Please continue to refer to Table 2. Compared with Example 1, the temperature distribution between the battery components in Example 2 is consistent with that in Example 1, but the colors of the battery components in Example 2 all change toward higher temperature colors. It is speculated that since the battery in Example 2 uses a higher rate discharge, the heat generation is increased compared with Example 1, but since the total heat dissipation capacity of the battery remains unchanged, the battery temperature in Example 2 is generally higher than that in Example 1.
[0097] Please continue to refer to Table 2. In Comparative Example 1, only the diaphragm shows color, and Comparative Example 1 and Example 1 use the same test method and parameters, but the color of the diaphragm in Comparative Example 1 is obviously different from that in Example 1, and the diaphragm temperature in Comparative Example 1 is obviously higher than that in Example 1. It is speculated that: since Comparative Example 1 is to coat the mixed solution containing microcapsules only on the diaphragm, and the microcapsules in Example 1 are distributed to various parts of the battery by the flow of the electrolyte, the temperature distribution of other structural parts inside the battery cannot be viewed in Comparative Example 1; further, since the microcapsules in Comparative Example 1 are coated on the surface of the diaphragm, they will increase the internal resistance of the diaphragm, thereby increasing the total internal resistance of the battery. According to Joule's law, Q=I 2 It can be seen from RT that it will eventually increase the heat generation, so the temperature it displays will be higher than the actual temperature. Example 1 uses electrolyte to disperse microcapsules, and the dispersion path conforms to the dynamic principle of the battery itself, which can more accurately reflect the temperature of various places inside the battery.
[0098] 2. The cylindrical batteries of Example 1 (Group A) were selected, and the cylindrical batteries with normal liquid injection (the electrolyte adopts the basic electrolyte in Example 1) (Group B) were used as the control. Two of each group were selected to test the performance of the batteries (capacity basically at 30Ah, voltage 3.65V, ohmic internal resistance: 1.6mΩ), including the short-term performance DCR (direct current internal resistance), rate discharge performance, and room temperature cycle performance of the two groups of batteries.
[0099] 2.1. DCR test: 1C charge to 4.25V, cut-off current is 0.05C, stand for 120min, 2C discharge to 10s, stepping interval is 0.1s, record data; adjust capacity value 50% SOC, 20% SOC, stand for 120min, 2C discharge to 10s, record data as shown in Table 3, where A1 and A2 represent the two cylindrical batteries in Example 1, and B1 and B2 represent the two cylindrical batteries with normal filling.
[0100] Table 3
[0101]
[0102]
[0103] 2.2. Rate discharge test: charge to 4.25V at 1C, with a cut-off current of 0.05C, let stand for 30 minutes, then discharge to 2.5V at 1C, and let stand for 120 minutes; charge to 4.25V with the same charging procedure, then discharge to 2.5V at 2C / 3C, record the capacity value, and calculate the capacity retention rate; the test results are shown in Table 4, in Ah, where A3 and A4 represent the two cylindrical batteries in Example 1, and B3 and B4 represent the two cylindrical batteries with normal filling.
[0104] Table 4
[0105] 1C 2C 3C 2C / 1C 3C / 1C A3 30.0 29.3 28.5 97.76% 95.00% A4 29.9 29.1 28.2 97.40% 94.29% B3 29.8 29.1 28.3 98.02% 95.28% B4 29.9 29.0 28.3 97.07% 94.62%
[0106] 2.3 Cycle performance: 25℃, cycle steps: 1C charge to 4.25V, cut-off current is 0.05C, stand for 30min, 1C discharge to 2.5V, stand for 30min, when the capacity drops to 95%, stop the cycle. Test results are as follows Figure 2 As shown, A5 represents the cylindrical battery in Example 1, and B5 represents the cylindrical battery with normal liquid injection.
[0107] The above test results show that the short-term and long-term performance of the battery does not deteriorate after adding the temperature-indicating particles. It is generally believed that adding substances to the electrolyte will reduce the conductivity of the electrolyte, which will reduce the transmission speed of lithium ions in the electrolyte, which is manifested as DCR becoming larger and the rate performance and cycle performance becoming worse. In the present invention, since the addition ratio of the temperature-indicating particles is low, and the temperature-indicating particles in the electrolyte are attached to the surface of the diaphragm, the shell, the cover plate and the surface of the positive electrode column after being injected into the battery, the transmission speed of lithium ions in the electrolyte will not be reduced, so the rate performance and room temperature cycle performance of the battery will not decrease, and the DCR will not increase.
[0108] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An electrolyte, characterized in that: It comprises a basic electrolyte and temperature-indicating particles, wherein the temperature-indicating particles are of a core-shell structure, comprising a temperature-indicating material and a shell that wraps the temperature-indicating material, wherein the shell is insoluble in the basic electrolyte; the temperature-indicating material is dispersed to various parts of the battery through the flow of the basic electrolyte, and the maximum temperature reached at different parts of the battery is calibrated by utilizing the irreversible change of the color of the temperature-indicating material as the temperature changes; the mass ratio of the temperature-indicating particles to the basic electrolyte is 1:10-20.
2. The electrolyte according to claim 1, characterized in that The D50 of the temperature indicating particles is 10-60 μm.
3. The electrolyte according to claim 1, characterized in that The temperature indicating material comprises copper sulfate and manganese sulfate; and the shell comprises polymethyl methacrylate.
4. A method for preparing the electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are included: S1: mixing an aqueous solution of a temperature indicating material with a polymethyl methacrylate solution to obtain an inner emulsion; S2: adding the inner emulsion to the outer emulsion for emulsification to obtain a mixed solution, wherein the outer emulsion is an oil phase solvent containing an emulsifier; S3: performing rotary evaporation on the mixed solution, standing for stratification, removing the oil layer, and obtaining a thermometric particle emulsion; S4: separating and drying the temperature-indicating particle emulsion to obtain temperature-indicating particles; S5: dispersing the temperature indicating particles in a basic electrolyte to obtain the electrolyte.
5. The preparation method according to claim 4, characterized in that: In the aqueous solution of the temperature indicating material, the content of the temperature indicating material is 10-20wt%; in the polymethyl methacrylate solution, the content of polymethyl methacrylate is 10-20wt%.
6. The preparation method according to claim 4 or 5, characterized in that: In the inner emulsion, the mass proportion of the aqueous solution of the temperature indicating material is 33-75%.
7. The preparation method according to claim 4, characterized in that: The oil phase solvent is selected from one or more of paraffin, alkyl phosphate, sulfonated fatty acid ester and polyacrylate; and the content of the emulsifier in the external emulsion is 8-10wt%.
8. The preparation method according to claim 4, characterized in that: In step S2, the volume of the inner emulsion accounts for 30%-70% of the volume of the mixed solution.
9. A battery, characterized in that: The invention comprises the electrolyte described in any one of claims 1 to 3 or the electrolyte prepared by the preparation method described in any one of claims 4 to 8.
Citation Information
Patent Citations
Lithium ion battery composite diaphragm as well as preparation method and application thereof
CN113948820A
Method for determining infiltration state of lithium ion battery electrolyte
CN110148793A
Preparation method of lithium ion battery diaphragm
CN115224436A